Clinical Practice Guideline for Tripterygium Glycosides/Tripterygium wilfordii Tablets in the Treatment of Rheumatoid Arthritis - Lin, Na; Zhang, Yan-Qiong; Jiang, Quan; Liu, Wei; Liu, Jian; Huang, Qing-Chun; Wu, Kuan-Yu; Tu, Sheng-Hao; Zhou, Zu-Shan; Chen, Wei-Heng; Li, Xiao-Xia; Ding, Ying; et al. (Frontiers in Pharmacology, 2021)
Tripterygium wilfordii Hook F (TwHF) is one of the most commonly used and effective traditional Chinese herbal medicine against rheumatoid arthritis (RA). Both Tripterygium Glycoside Tablets (TGT) and Tripterygium Wilfordii Tablets (TWT) are the representative TwHF-based agents enrolled into the 2019 edition of Medicine Catalogue for National Basic Medical Insurance, Injury Insurance and Maternity Insurance. However, individual differences in TGT/TWT response across patients usually exist in the process of treating RA, implying that the clinical application of the two agents may not be standardized leading to the ineffective treatment and the risk of side effects. Growing evidence show that the bioactive constituents of TwHF may often have toxicity, the package insert of TGT and TWT may not be described in details and the therapeutic windows of the two agents are narrow. Thus, it is an urgent task to develop a standardized clinical practice guideline for TGT and TWT in the treatment of RA. In the current study, a group of clinical experts of traditional Chinese medicine and Western medicine in the research field of rheumatism diseases, pharmacists and methodologists of evidence-based medicine were invited to select the clinical questions, to determine the levels of the evidence and the strength of the recommendations, and to develop the recommendations and good practice points. The guideline is formed based on the combination of clinical research evidence and expert experience (evidence-based, consensus, supplemented by experience). The clinical problems which are supported by clinical evidence may form recommendations, and the clinical problems without clinical evidence may form experts' suggestions. Both recommendations and experts' suggestions in this guideline summarized the clinical indications, usage, dosage, combined medication and safety of TGT and TWT against RA systematically and comprehensively, which may offer a professional guidance in the context of the clinical application of the two TwHF-based agents.